Evaluation of chemical and physical characteristics of pumpkin flour (Cucurbita maxima): pulp and seeds (Research, Society and Development, 2022)
The pumpkin pumpkin (Cucurbita maxima) is popular in Brazil and is among the three varieties that stand out with the highest consumption in the country. Pumpkin pulp is considered to be rich in natural antioxidants, carotenoids. Humans do not synthesize this pigment, so the need for it is satisfied by eating foods containing carotene. The seeds also have carotenoid content, in addition to total phenolics, flavonoids and mineral content, highlighting the amount of Zinco. In addition to the products already on the market, based on pumpkin pumpkin, there is also the potential for pumpkin flour to be used as an ingredient in breads, baked goods and gluten-free pasta. The objective of this work was the development of pumpkin pulp and seeds flour, seeking the best time/temperature binomial for dehydration and physicochemical analysis. The pulp flour moisture was considered within the limits established by Anvisa. The ash value did not differ between the pulp and seed flour samples. The protein content was higher in the seed flour, as well as the titratable acidity and the total fiber content. The mineral composition of the seed meal stood out due to the high content of Zinco. From the drying curves it was possible to observe that the higher temperature allowed a shorter drying time, which would make it better economically. The flours had a high content of minerals and organic matter which make them an attractive and viable commercial alternative.